2000
DOI: 10.1186/1471-2296-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Are the pneumococcal polysaccharide vaccines effective? Meta-analysis of the prospective trials

Abstract: The objective was to review the evidence of effectiveness of the polyvalent polysaccharide pneumococcal vaccine from prospective properly randomised controlled trials comparing pneumococcal vaccines with placebo in subjects who are immunocompetent and those likely to have an impaired immune system.Databases searched included the Cochrane Library, (issue 2, 2000), MEDLINE (1966-August 2000), PubMed (to August 2000) and EMBASE ( to August 2000). Reference lists of reports and reviews were also searched. To be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0
4

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(56 citation statements)
references
References 38 publications
3
49
0
4
Order By: Relevance
“…Several meta-analyses reported protective effects of the vaccine on all-cause pneumonia in subgroups, for example lowrisk groups or populations from lower income countries. 11,16,19 Some previous meta-analyses agreed with our finding of no compelling evidence for the vaccine being associated with a reduced risk of all-cause pneumonia, particularly among elderly or chronically ill people. 7,16,17,19,22 Conclusions for other outcomes were often conflicting, especially for invasive pneumococcal disease.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Several meta-analyses reported protective effects of the vaccine on all-cause pneumonia in subgroups, for example lowrisk groups or populations from lower income countries. 11,16,19 Some previous meta-analyses agreed with our finding of no compelling evidence for the vaccine being associated with a reduced risk of all-cause pneumonia, particularly among elderly or chronically ill people. 7,16,17,19,22 Conclusions for other outcomes were often conflicting, especially for invasive pneumococcal disease.…”
Section: Discussionsupporting
confidence: 80%
“…11,16,19 Some previous meta-analyses agreed with our finding of no compelling evidence for the vaccine being associated with a reduced risk of all-cause pneumonia, particularly among elderly or chronically ill people. 7,16,17,19,22 Conclusions for other outcomes were often conflicting, especially for invasive pneumococcal disease. A recent Cochrane review 7 found strong evidence supporting the vaccine's efficacy against invasive pneumococcal disease, reporting a combined odds ratio of 0.26 (95% CI 0.15-0.46).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The efficacy of the pneumococcal polysaccharide vaccine has been evaluated in five meta-analyses, or systematic reviews [314][315][316][317][318]. The quality, as well as the results, of these metaanalyses/systematic reviews differs, due to when they were performed and differences in methodology.…”
Section: Is the Vaccine Safe?mentioning
confidence: 99%
“…Para ello seleccionaron trece estudios de las características señaladas en los que además se reflejaran hechos clínicos relevantes como las tasas de neumonía global, neumonía neumocócica, de infección respiratoria baja, bacteriemia y muertes por neumonía. Concluyen que este tipo de vacunas son efectivas en la población inmunocompetente para disminuir la incidencia global de neumonías y el resto de las tasas mencionadas y que en cambio no existe evidencia de beneficio para la población con alguna alteración del sistema inmune 8 . Sin e m b a rgo, debido a las diferencias en la capacidad del sistema inmunitario para hacer frente a la infección neumocócica, la efectividad de estas vacunas varía según el tipo de inmunodepresión, por lo que estos ensayos deberían estar categorizados según las características de los pacientes estudiados para poder establecer comparaciones.…”
unclassified